Medicine and Ethics in Black Women’s Speculative Fiction - Jones, Esther L. author. aut Link
X, 190 p.
Keywords: Speculative fiction often shows the complicated and rather fraught history of medicine as it relates to black women. Through prominent writers like Octavia Butler, Nnedi Okorafor, and Nalo Hopkinson, Jones highlights how personal experiences of illness and disease frequently reflect larger societal sicknesses in connection to race and gender.